CORRELATES OF NON-ADHERENCE TO HOME EXERCISE PROGRAMMES IN PATIENTS WITH LOW BACK PAIN - ODEBIYI, DO; FAPOJUWO, OA; OLALEYE, BF; OLANIYAN, AS (International Journal of Research -GRANTHAALAYAH, 2020)
Background: Non-adherence to home exercise programmes may lead to delayed progress in recovery and diminished clinical outcomes in patients. Aims of Study: To determine the adherence rate and attributing factors to non-adherence to home exercise programmes in patients with low back pain (LBP). Method: A total of 250 patients with LBP receiving treatment in 5 different out-patient physiotherapy clinics in Lagos State South West, Nigeria participated in this survey. They were required to complete a 27- item questionnaire which collected information on characteristics of participants and home exercise programme, adherence with treatment programme and instructions for carrying out the exercises. Gamma correlation and Chi-square were used to detect the correlation and significant difference of selected variables respectively. The level of significance was set at p< 0.05 Result: Ninety-four (37.6%) respondents performed home exercise programme the recommended number of times daily. There was no significant relationship (p> 0.05) of participants’ characteristics, frequency and duration of exercise per session, total number and manner of recommending the home exercise programme and pain rating respectively with adherence to home exercise programme. Eighty-nine (35.6%) respondents complained of tiredness after the day’s work. Chi-square showed significant association (p<0.05) of the prescribed home exercises programme, the actual exercise carried out at home with their perception to home exercise programme Conclusion: Home exercise programmes may interfere with normal life and daily routine in patients with LBP. It is recommended that home exercise programme be patient centred I.e. fit into individual daily routine to overcome identified barriers.